(untitled) (Journal of Atomic and Molecular Sciences, 2015)
A four-degrees-of-freedom, time-dependent quantum wave packet propagation method is employed to study the F+CD_4→DF+CD_3 reaction. The calculations show a common resonance peak appears in the reaction probabilities, which verifies the prediction of such resonance from experiment. For F+CD_4, the vibrational excitations of the C-H stretching mode enhance the reactivity, whereas the C-X umbrella vibrational excitations hinder the reaction; and the translational energy is more effective than vibrational energy at very lower collision energy, and less effective than the vibrational energy at most energy range. So for this endoergic early barrier reaction, the Polanyi rules cannot be extended to this poly-atomic reaction except at very low collision energy.